2016
DOI: 10.1080/09712119.2016.1256292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protease and phytase supplementation on growth performance and nutrient digestibility of rainbow trout (Oncorhynchus mykiss, Walbaum) fed soybean meal-based diets

Abstract: An experiment was conducted to evaluate effects on growth, body composition and nutrient digestibility of addition protease and phytase to soybean meal-based diet in rainbow trout. Seven soybean meal-based diets were prepared by adding protease, phytase and mixture of both enzymes at two different levels (1 and 2 g kg −1 ) to a base diet without enzymes. Mixed enzymes (1, 2 g kg −1 ) were prepared by adding protease and phytase at the same doses (0.5 + 0.5 and 1 + 1 g kg −1 ). Diets consisted of 31% fish meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 17 publications
0
32
1
1
Order By: Relevance
“…On the other hand, Dalsgaard et al (2012) found no significant differences in growth parameters and FCR of rainbow trout, Oncorhynchus mykiss, while ADC of protein moderately improved due to the addition of protease to soybean meal diet. Yigit et al (2018) found that protease supplementation to rainbow trout had no significant effect on growth, FCR, and protein and dry matter digestibility. Yigit et al (2018) found that protease supplementation to rainbow trout had no significant effect on growth, FCR, and protein and dry matter digestibility.…”
Section: Fingerlings Growth and Survivalmentioning
confidence: 89%
See 2 more Smart Citations
“…On the other hand, Dalsgaard et al (2012) found no significant differences in growth parameters and FCR of rainbow trout, Oncorhynchus mykiss, while ADC of protein moderately improved due to the addition of protease to soybean meal diet. Yigit et al (2018) found that protease supplementation to rainbow trout had no significant effect on growth, FCR, and protein and dry matter digestibility. Yigit et al (2018) found that protease supplementation to rainbow trout had no significant effect on growth, FCR, and protein and dry matter digestibility.…”
Section: Fingerlings Growth and Survivalmentioning
confidence: 89%
“…Ayhan et al (2008) also reported that the addition of protease to soybean meal diets for gilthead seabream (Sparus aurata) larvae had no effect on growth and protein digestibility. Yigit et al (2018) found that protease supplementation to rainbow trout had no significant effect on growth, FCR, and protein and dry matter digestibility.…”
Section: Fingerlings Growth and Survivalmentioning
confidence: 89%
See 1 more Smart Citation
“…However, in some fish, dietary phytase may exhibit insignificantly or none effect on the growth performance and feed efficiency. For instance, the supplementation of phytase did not significantly enhance the growth response of Japanese sea bass, which was consistent with the results that the addition of phytase to diets including soybean meal does not affect growth and FCR in rainbow trout (Yigit et al, ), and the addition of phytase to diet containing soybean meal in seabream had no effect on the growth performance (Ayhan et al, ). Sajjadi & Carter () also stated that no effect on growth and feed efficiency was observed after phytase supplemented to diet (canola meal) of Atlantic salmon.…”
Section: Exogenous Enzymes Currently Used In Fishmentioning
confidence: 99%
“…In spite of this, this speculation was not absolutely correct. In some cases, the addition of protease and phytase to the basic diet had no significant effect on the growth parameters, FCR and nutrient digestibility of rainbow trout (Yigit et al, ). A multienzyme (Superzyme CS: xylanase, amylase, cellulase, protease and β‐glucanase) introduced into diet of rainbow trout showed no significant effect on the growth performance (Ogunkoya et al, ).…”
Section: Perspectives and Opportunities For Exogenous Enzyme Supplemementioning
confidence: 99%